Adaptive Management Tools: Concept Notes System - Mercy Corps (Mercy Corps, 2015)
Mercy Corps finds adaptive management is supported by four different but interconnected elements: Culture, People & Skills, Tools & Systems, and Enabling Environment. These elements are discussed in the context of one of Mercy Corps’ complex programmes in pastoral Ethiopia.

Learning to Adapt: Exploring Knowledge, Information and Data for Adaptive Programmes and Policies - Workshop Summary Report - fhi360 (IDS, 2015)
Adaptive management is increasingly seen as critical capability for development programmes and policies that are more effective, efficient, relevant and sustainable. There is increasing recognition that such work requires significant changes to the organizational structures, management processes, accountability and performance cultures and indivi

Adapting development: improving services to the poor - Wild, Leni; Booth, David; Cummings, Clare; Foresti, Marta; Wales, Joseph (ODI, 2015)
On current trends, it will take decades or longer to bring basic services to the world’s most disadvantaged people. Meeting this challenge means recognising the political conditions that enable or obstruct development progress - a radical departure from the approach of the Millennium Development Goals.
Keywords: Practice

How can we be more adaptive? AdaptScan identifies critical areas for improvement - Mercy Corps (Mercy Corps & IRC, 2017)
Keywords: IMPORTANT

Adapting Aid: Lessons from six case studies - Algoso, Dave; Beloe, Jon; Hemberger, Alison; Hill, Philippa; Proud, Emma (MercyCorps & IRC, 2016)
Keywords: IMPORTANT

Monitoring, Evaluation and Learning in NGO Advocacy - Findings from Comparative Policy Advocacy MEL Review Project - Coe, Jim; Majot, Juliette (ODI and Oxfam, 2013)
For organizations committed to social change, advocacy often figures as a crucial strategic element. How to assess effectiveness in advocacy is, therefore, important. The usefulness of Monitoring, Evaluation and Learning (MEL) in advocacy are subject to much current debate. Advocacy staff, MEL professionals, senior managers, the funding community, and stakeholders of all kinds are searching for ways to improve practices – and thus their odds of success – in complex and contested advocacy environments. This study considers what a selection of leading advocacy organizations are doing in practice. We set out to identify existing practice and emergent trends in advocacy-related MEL practice, to explore current challenges and innovations. The study presents perceptions of how MEL contributes to advocacy effectiveness, and reviews the resources and structures dedicated to MEL.

One step back, two steps forward: CARE’s journey towards doing development differently - Aston, Tom (Care Insights, 2017)
The Doing Development Different (DDD) community emerged in August 2014 and advocates that (a) the barriers to development are as much political as tec...

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (USAID LEARN, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

NGOs Doing Development Differently - Green, Duncan (From Poverty to Power, 2017)
Report back from a meeting of international NGOs to set up a research and practice network on 'Doing Development Differently' that can complement other actors

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT